Long-term psychological intervention for parents of children with prolonged disorders of consciousness: a pilot study - Xu, Gang; Hao, Fuchun; Zhao, Weiwei; Zhao, Peng; Qiu, Jiwen (Frontiers in Psychology, 2023)
Background Children with prolonged disorders of consciousness experience severe intellectual and behavioral disabilities that will last for decades or even a lifetime. Parents generally experience severe anxiety, stress, sadness, or family conflicts, which can lead to abnormal parenting behavior and can, in turn, adversely affect the cognitive, emotional, and behavioral well-being of the children. This causes a serious burden on children, families, and society. Psychological interventions targeting parents using online conversations provide an opportunity to improve the overall well-being of the parents, their children, and the family as a whole. Methods A total of 13 patients completed the protocol. Six were girls (46.2%), the mean age was 4.5 ± 3.0 years, and the length of time before emergent from minimally consciousness state was 244 ± 235 days. A staff member with psychological counseling qualifications implemented all psychological interventions. Regular online psychological interventions were performed annually before and after discharge. Evaluation data were collected before discharge and at 1 and 3–5 years post-discharge. Results With the extension of intervention time, the Strengths and Difficulties Questionnaire, the Depression Anxiety and Stress Scale-21, and the Parenting Sense of Competence Scale scores showed significant improvement (p < 0.05), while the Revised Scale for Caregiving Self-Efficacy scores did not. With the extension of intervention time, the Strengths and Difficulties Questionnaire (Total Difficulties scores, TD) scores showed significant improvement (p < 0.05), while the scores did not after 1 year compared with before intervention. The Index of Child Care Environment evaluation scores declined significantly (p < 0.05). Conclusion Psychological interventions aimed at the parents of children with prolonged disorders of consciousness performed at least once per year resulted in significant improvements in negative parental emotions, parental self-efficacy, and emotional and behavioral problems in their children. However, the childcare environment continued to decline.